Manajemen Risiko Pada Pembiayaan Mudharabah di Bank Syariah Pamekasan (Studi Atas Bank Perkreditan Syariah) - Rafi Samsuri (Universitas Muhammadiyah Surabaya, 2018)
This thesis intends to reveal empirically about the implementation of management to overcome the risk of loss in distributing mudharabah financing in Sharia Credits Banking Bhakti Sumekar Pamekasan. In this study, the authors focused on the subject matter which is how sahib al-mal in Bhakti Sumekar Pamekasan minimized the risk in mudharabah financing, with the aim to explain and analyze the management system used in controlling the risk of mudharabah financing.Overall, this anaysis was conducted based on data and information obtained in the field through interviews, sessions of various relevant documentation, and through direct observation activities. To analyze these problems, the authors used the method of comparative-explorative descriptive approach as a means of analysis. From the results of the existing analysis, it can be concluded that the risk of measurement system in distributing mudharabah financing in Sharia Banking Bhakti Sumekar Pamekasan was measuring the risk of the type of project finance; whether it had high risk, high failure , or have minimal failure or minimal risk. Risk measurement was also done by looking at the internal condition of the company either from aspects of management, marketing, technical production, or financial data in the form of cash flow. The monitoring or monitoring system used by Sharia Banking Bhakti Pamekasan in distributing mudharabah financing were two patterns (1) on desk monitoring or supervision of administrative data, and (2) on site monitoring that directly go to the business location mudarib or inspection on the spot.Â Â Keywords: Financing, Akad Mudharabah, Risk Menejement